The Energy Processing by Power Electronics and its Impact on Power Quality - Rocha, J.E.; Sanchez, W.D.C (Center of Biomass & Renewable Energy, Diponegoro University, 2012)
This paper discusses the electrical architectures adopted in wind turbines and its impact on the harmonic flux at the connected electric network. The integration of wind electric generators with the power grid needs energy processing by power electronics. It shows that different types of wind turbine generator systems use different types of electronic converters. This work provides a discussion on harmonic distortion taking place on the generator side, as well as in the power grid side.Â Keywords: grid connection, harmonic distortion, power electronics and converters, wind energy conversion systems, wind power, wind technology, wind turbines